2012
DOI: 10.1186/1756-0500-5-69
|View full text |Cite
|
Sign up to set email alerts
|

Rapid multiplex high resolution melting method to analyze inflammatory related SNPs in preterm birth

Abstract: BackgroundComplex traits like cancer, diabetes, obesity or schizophrenia arise from an intricate interaction between genetic and environmental factors. Complex disorders often cluster in families without a clear-cut pattern of inheritance. Genomic wide association studies focus on the detection of tens or hundreds individual markers contributing to complex diseases. In order to test if a subset of single nucleotide polymorphisms (SNPs) from candidate genes are associated to a condition of interest in a particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…While Seipp et al 17 used GC-rich and AT-rich tailed primers as well as primers incorporating locked nucleic acids to achieve ample gaps between the melt curves of the target amplicons, Pereyra et al 18 designed conventional, non-modified primer pairs to amplify targets of 50–200 bp long, simply using product sizes to achieve adequate separation of melt curve Tms. These have been reasonably successful but they are single-stage reactions which increases the risk of inappropriate primer interaction.…”
Section: Discussionmentioning
confidence: 99%
“…While Seipp et al 17 used GC-rich and AT-rich tailed primers as well as primers incorporating locked nucleic acids to achieve ample gaps between the melt curves of the target amplicons, Pereyra et al 18 designed conventional, non-modified primer pairs to amplify targets of 50–200 bp long, simply using product sizes to achieve adequate separation of melt curve Tms. These have been reasonably successful but they are single-stage reactions which increases the risk of inappropriate primer interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that transcription factors can bind a few specific sites located in the promoter and intron regions of genes to influence gene expression (Myers et al, 2007;Pereyra et al, 2012) and protein translation (Down et al, 2012). However, the exact functions of SNPs in non-coding regulatory regions are not clear, but are predicted to influence the binding affinity of transcription factors (Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that inflammation is associated with SPTB [10], [11], [12]. During recent years, the link between polymorphisms in genes encoding cytokines involved in inflammatory mechanisms has received increased attention from researchers [4], [5], [6], [7]. However, no study has yet explored association between SPTB and SEPS1, which is an upstream regulatory factor of inflammatory cytokine [14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are significant racial/ethnic disparities in the incidence of SPTB, with African Americans running more than twice as great a risk of SPTB as European-American women. In addition, association studies have identified a number of genetic polymorphisms related to infection, inflammation and innate immune systems that are risk factors for SPTB [4], [5], [6], [7], [8], [9]. Despite these advances, the alleles accounting for the bulk of genetic susceptibility to SPTB remain undiscovered, particularly in Chinese populations.…”
Section: Introductionmentioning
confidence: 99%